Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

A variant method of squeezed rejection algorithm for the simulation of the exponential distribution $\exp(1)$ truncated to $(0,2)$ interval can be written as:

(a) generate $Y \sim U(0,2)$ , $U\sim U(0,1)$

(b) if $U \le \mathrm{e}^{-a} \times (a+1-Y)$ go to (e)

(c) if $U> \mathrm{e}^{-b}/(1-b+Y)$ go to (a)

(d) if $U> \mathrm{e}^{-Y}$ go to (a)

(e) set $X=Y$

Prove that the probability of success in step (b) is equal to $a \times \mathrm{e}^{-a}$ if $a\ge 1$ and equal to $1/4 \times (a+1)^2 \times \mathrm{e}^{-a}$ if $a<1$. Prove that the best choice is $a=1$

a,b>0 (a,b)εΝ

share|improve this question
If this is homework, tag as such, and show us what you have tried. –  leonbloy Nov 13 '11 at 20:01
i'm not exactly sure how to start.i would appreciate if you could help me. –  Panagiotis Nov 13 '11 at 20:14
@Panagiotis I edited your question using LaTeX for math. Please see if my interpretation of what square brackets meant is correct. –  Sasha Nov 13 '11 at 20:23
@Panagiotis Also could you define symbol $b$ used in step (c) ? –  Sasha Nov 13 '11 at 20:28
@Sasha thank you,it's much better like this..it's my first post. –  Panagiotis Nov 13 '11 at 20:28

1 Answer 1

Here are some hints:

  • Show that for all $0 < a < 2$, $0<b<1$ and $0<y<2$, $$ \mathrm{e}^{-a} (a-y+1) \leq \mathrm{e}^{-y} \leq \frac{\mathrm{e}^{-b}}{y+1-b} $$ To this end, use $1+x \le \exp(x)$, valid for all $x \in \mathbb{R}$. Change $x \to -x$, and restricting to $1-x > 0$, derive $\exp(x) \le\frac{1}{1-x}$.

  • Compute $\mathbb{P}( U \le \mathrm{e}^{-a} (a-Y+1))$. Notice that $F_U(u) = \mathbb{P}(U \le u) = \min(\max(u,0),1)$. Then use: $$ \begin{eqnarray} \mathbb{P}(U \le \mathrm{e}^{-a} (a-Y+1)) &=& \mathbb{E}( F_U(\mathrm{e}^{-a} (a-Y+1)) ) = \mathbb{E}(\min(\max( \mathrm{e}^{-a} (a-Y+1) ,0),1) ) \\ &=& \int_0^2 \min(\max( \mathrm{e}^{-a} (a-Y+1) ,0),1) \, \frac{1}{2} \mathrm{d}y \\ &=& \int_{0}^{\min(2,a+1)} \mathrm{e}^{-a} (a-Y+1) \frac{1}{2} \mathrm{d}y \end{eqnarray} $$

  • Finish the calculations, then maximize the function.

Here are some visual clues:

enter image description here

share|improve this answer
could you please explain what exactly are you doing here "To this end, use 1+x≤exp(x), valid for all x∈R. Change x→−x, and restricting to 1−x>0, derive exp(x)≤11−x." Thank you very much for your help the rest is quite understandalbe. –  Panagiotis Nov 14 '11 at 0:28
@Panagiotis I meant replace in $1+y \le \exp(y)$, $y$ with $-x$, to get $1-x \le \exp(-x)$. Now, assuming $1-x > 0$, reciprocate and get $\frac{1}{1-x} \ge \frac{1}{\exp(-x)}$ which gives $\exp(x) \le \frac{1}{1-x}$. –  Sasha Nov 14 '11 at 2:47
ok. i got it.again,thanks for your help. –  Panagiotis Nov 14 '11 at 22:33

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.